The periodicity and duration of oestrus in zebu and grade cattle - Anderson, J. (Cambridge University Press, 1944)
Records are given for 1130 oestrous cycles in zebus and 678 cycles in grades. The mean length was 23·03 days in zebus and 22·42 days in grades. The mean duration of oestrus was 4·78 hr. in zebus. 7·40 hr. in grades. Neither exposure to additional light at night nor feeding a supplementary ration had any effect on the cycle of oestrus.Seasonal variations in both the cycle and oestrus occurred in zebus, but in grades they were much less marked. An association between climatic conditions and sexual function was noted in that a season of increased temperature and sunshine was associated with increased sexual function and vice versa.